Komodifikasi Pesan Dakwah Pada Iklan Pertamina Versi Tabungan Terbaik di Televisi - Huda, Miftahul (Institut Agama Islam Negeri (IAIN) Curup, 2018)
In this study, The researcher discussed about the commodification of da'wah messages on pertamina ads, the best savings version. This study included a type of qualitative research using S Jager and F Maier's critical discourse analysis methods by making a synopsis, determining the main characters, discursive practices, non-discursive practices, object materialization, and theorizing of advertising themes. Based on the results of the analysis, it was found that there were signs that identified the practice of commodification of da'wah messages on the best savings version of pertamina ads in the form of images, conversations, and texts in the description of the ad stories. The message of commodified da'wah becomes a narrative that charity will be a shelter for humans when in the hereafter. The missionary message was conveyed in order to increase knowledge, change attitudes and mindset of the community and convey corporate messages so that people are economical in using fuel and not too consumptive in buying motorcycles. The researcher concluded that da'wah messages which are noble religious messages in order to change human beings for the better and get happiness in the world and the hereafter can be packaged and utilized as a matter for transforming values into exchange values that are image-building for corporate interests.